Outcomes and Complications of Sutured Scleral-Fixated Foldable Intraocular Lens Implantation: A Retrospective Study of 5-Year Follow-Up - Ting Yu; Mengting Yu; Wenjie Wu; Xinna Wu; Suzhen Xiao; Jialiang Mao; Yanling Wang (Journal of Ophthalmology)
Purpose. To evaluate long-term outcomes and complications of sutured scleral-fixated foldable intraocular lens (IOL) implantation. Design. Retrospective study. Methods. Patients who underwent sutured scleral-fixated foldable IOL implantation using 10-0 polypropylene suture were followed up for at least 5 years at one Chinese tertiary hospital and two primary hospitals. Results. 52 eyes among 48 patients (35 male and 13 female) were evaluated. The mean age (years) was 50.27 ± 20.08 (range: 6 to 81). The mean postoperative follow-up time (months) was 79.70 ± 18.84 (range: 60 to 121). The mean best-corrected visual acuity (BCVA) improved from 0.83 ± 0.69 logarithm of the minimum angle of resolution (logMAR) at baseline to 0.50 ± 0.45 logMAR at the last follow-up visit. There was improved or unchanged BCVA in 44 eyes (84.62%) and reduced BCVA in 8 eyes (15.38%). Mild intraoperative intravitreal hemorrhage was observed in 3 eyes (5.77%). Early postoperative complications included transient elevated intraocular pressure (IOP) in 5 eyes (9.62%) and hypotony in 1 eye (1.92%). Secondary epimacular membrane occurred in 5 eyes (9.62%) and retinal detachment (RD; 3 years postsurgery), subconjunctival suture knot exposure (5 years postsurgery), and persistent elevated IOP (in a GRAVES patient) occurred in 1 eye (1.92%) each. No suture erosion or breakage nor IOL dislocation was observed. No visually threatening IOL tilt or decentration was reported in any patient. Conclusion. Sutured scleral-fixated foldable IOL implantation demonstrated satisfactory long-term outcomes and rare suture-related complications. This technology was safe and did not require complicated equipment and is of considerable interest in the setting of aphakia without adequate capsule support.